Long-term outcomes of deceased donor liver transplantation in hepatocellular carcinoma patients with portal vein tumor thrombus: A multicenter study. Issue 1 (January 2022) - Yu, Jiongjie; Zhuang, Li; Liu, Peng; Liu, Zhikun; Ling, Sunbin; Deng, Yinan; Li, Jianhua; Yang, Bo; Chen, Zhishui; Wang, Zhengxin; Zang, Yunjin; Yang, Yang; et al.
Abstract: Background: The incidence of portal vein tumor thrombus (PVTT) has been reported to be as high as approximately 10%–40% in patients with hepatocellular carcinoma (HCC). The long-term prognosis of deceased donor liver transplantation (DDLT) in HCC patients with PVTT remains unknown. Methods: Data of 961 HCC patients who underwent DDLT between 2015 and 2018 in six centers were analyzed. Based on the Milan criteria (MC) and Cheng's classification of PVTT, the patients were divided into 4 groups: within MC, beyond MC without PVTT, type 1 PVTT, and type 2 PVTT groups. Results: 489 (50.9%) were within the MC, 296 (30.8%) beyond the MC but without PVTT, 83 (8.6%) type 1 PVTT, and 93 (9.7%) type 2 PVTT. Kaplan-Meier analysis showed that type 1 or 2 PVTT patients with alpha-fetoprotein (AFP) ≤ 100 ng/mL had overall survival (OS) similar to that of patients within the MC ( P = 0.957), and superior OS ( P = 0.003 and 0.009) and recurrence-free survival (RFS) ( P = 0.038 and <0.001) than those of patients beyond the MC and PVTT patients with AFP > 100 ng/mL. Multivariable Cox-regression analysis identified type 1 and 2 PVTT to be independent risk factor for RFS [hazard ratio (HR) 1.523 95% confidence interval (CI) 1.162–1.997, P = 0.002], but not for OS (HR 1.283, 95%CI 0.922–1.786, P = 0.139). Conclusion: HCC patients with type 1 or 2 PVTT may be acceptable candidates for DDLT. To achieve better outcomes, preoperative AFP levels should be seriously considered when selecting patients with PVTT for DDLT.